Innovation in Business and Enterprise 2010
DOI: 10.4018/978-1-61520-643-8.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Causation as Explanatory Theory for Innovation

Abstract: While numerous theories have been used to explain innovation, one found to be useful in recent years is cumulative causation. Its major focus on incremental and evolutionary change, the path dependent nature of change, and its circular and cumulative effects, make it particularly useful in helping to explain innovation. In this chapter the literature on cumulative causation theory is reviewed to highlight links between these characteristics of the theory and innovation, as well as influences such as problem so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, both firms and governments have recognised the importance of forging links with the tourism industry to promote wine regions and expand market opportunities (Getz and Brown, 2006). Established wineries such as De Bortoli Wines have tapped into wine tourism by purchasing existing wineries in tourism‐oriented regions including the Hunter, King, and Yarra Valleys, and by establishing other attractions such as function centres and restaurants at the newly purchased wineries (Bamberry, 2010; De Bortoli Wines, www.debortoli.com.au/). A similar partnership between the wine and tourism industries in New Zealand has been mutually beneficial ( Manawatu Standard , 2007).…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…However, both firms and governments have recognised the importance of forging links with the tourism industry to promote wine regions and expand market opportunities (Getz and Brown, 2006). Established wineries such as De Bortoli Wines have tapped into wine tourism by purchasing existing wineries in tourism‐oriented regions including the Hunter, King, and Yarra Valleys, and by establishing other attractions such as function centres and restaurants at the newly purchased wineries (Bamberry, 2010; De Bortoli Wines, www.debortoli.com.au/). A similar partnership between the wine and tourism industries in New Zealand has been mutually beneficial ( Manawatu Standard , 2007).…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…As innovation can be considered to be a form of change that often leads to broader organisational change, the findings of the Jordanian study suggest that it would be useful in our study of the influence of a learning culture in the Riverina firms to look for aspects of innovation that lead to organisational change. Previous work focusing on innovation in manufacturing in the Riverina Region has shown that small manufacturing enterprises have been a source of innovation that has contributed to the region's economic development (Bamberry, 2010). Similarly, at the national level, it was found that manufacturing has been a significant source of innovation in Australia over many years (Toner, 2000).…”
Section: Learning Culture and Organisational Changementioning
confidence: 97%
“…The region has a small but significant manufacturing sector, processing agricultural commodities grown mainly within the region, and producing capital goods for that sector (Bamberry, 2010). It also has a small number of manufacturing firms whose location in the region can be explained as "accidents of history" in that the entrepreneurs who established the businesses just happened to be working and living in the region.…”
Section: Introductionmentioning
confidence: 99%